2001
DOI: 10.1111/j.1572-0241.2001.03800.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress, Social Support, and Disease Activity in Patients With Inflammatory Bowel Disease

Abstract: These findings suggest that strategies aimed at improving social support can have a favorable impact on psychological distress and, ultimately, can improve health outcomes in patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(64 citation statements)
references
References 31 publications
5
58
0
1
Order By: Relevance
“…This finding supports other IBD studies, in that being single was associated with greater odds of being depressed, and the general sense of not being supported was related to poorer health-related QoL (Fuller-Thomson & Sullman, 2006;Graff et al, 2009;Moradkhani et al, 2013). Previous research has also shown social support to protect against the effects of pain, depression and stress in patients with IBD (Fuller-Thomson & Sullman, 2006;Sewitch et al, 2001). Previous studies suggest that age is an important determinant of IBD-QoL, with patients who are diagnosed before the age of 30 years old reporting poorer IBD-QoL than for those patients diagnosed after the age of 30, and those who are greater than 70 years of age to have a better QoL with fewer concerns (Canavan et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This finding supports other IBD studies, in that being single was associated with greater odds of being depressed, and the general sense of not being supported was related to poorer health-related QoL (Fuller-Thomson & Sullman, 2006;Graff et al, 2009;Moradkhani et al, 2013). Previous research has also shown social support to protect against the effects of pain, depression and stress in patients with IBD (Fuller-Thomson & Sullman, 2006;Sewitch et al, 2001). Previous studies suggest that age is an important determinant of IBD-QoL, with patients who are diagnosed before the age of 30 years old reporting poorer IBD-QoL than for those patients diagnosed after the age of 30, and those who are greater than 70 years of age to have a better QoL with fewer concerns (Canavan et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…As such, caution should be exercised when applying the results of this study to patients with IBD of other ethnicities and socioeconomic variations. However, the composition of our sample is representative of other IBD samples within the literature in regards to demographic composition (Drossman et al, 2000;Lix et al, 2008;Nurmi et al, 2013;Sewitch et al, 2001). Another limitation is the use of self-report questionnaires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A US American study with IBD patients (without IPAA) demonstrated a greater predictive value of the number and impact of stressful events than of disease activity for psychologic distress. 27 Some limitations of our study must be considered. The number of IPAA patients included in the study (n = 37) is rather low.…”
Section: Discussionmentioning
confidence: 96%
“…Four studies examined the role of perceived stress on adjustment outcomes, all cross sectional in design (Kiebles et al, 2010, Goodhand et al, 2012, Sewitch et al, 2001,Tabibian et al, 2015 ( were additional independent correlates of depression in CD (Goodhand et al, 2012, Tabibian et al, 2015. Examination of study quality (table 1) demonstrated that the small number of studies in this category were of low-moderate quality with scores between 3-4.…”
Section: Accepted Manuscriptmentioning
confidence: 99%